DEVELOPMENT OF MATHEMATICS TEACHINGS BASED ON APOS THEORY: CONSTRUCTION OF UNDERSTANDING THE CONCEPT OF STUDENT STRAIGHT LINE EQUATION - Kamid Kamid; Nizlel Huda; Rohati Rohati; Sufri Sufri; Dewi Iriani; Khairul Anwar (Ta'dib, 2021)
This research is an ADDIE-based research and development. Data on the development process were collected using tools validated by materiel experts, design experts, student response questionnaires and teacher responses. The results of the implementation of the use of textbooks are seen from the student activity sheets and student learning outcomes, in this study using participants from class VIII students of MTs YPI Kuala Enok totaling 28 students with a random sampling technique. The results of this development research are: (1) SMP / MTs mathematics textbooks based on the APOS theory on straight line equation material are declared suitable for use in learning activities based on the validation results of material experts and design experts. Based on the results of student and teacher responses to textbooks, they are ranked very well. (2) The effectiveness of using SMP/MTs mathematics textbooks based on the APOS (Action, Process, Object, Schema) theory of straight line equation material seen from the student activity sheet can be concluded that in the process of learning student activities. In addition, on the basis of the results of all students, the criteria for completeness were achieved, an average score of 85. Thus, from the results of this analysis, it can be concluded that textbooks based on the APOS theory are effective in constructing an understanding of the concept of straight line equations.